2017
DOI: 10.1038/bjc.2017.138
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of early prophylactic feeding vs standard care in patients with head and neck cancer

Abstract: Background:Weight loss remains significant in patients with head and neck cancer, despite prophylactic gastrostomy and intensive dietary counseling. The aim of this study was to improve outcomes utilising an early nutrition intervention.Methods:Patients with head and neck cancer at a tertiary hospital in Australia referred for prophylactic gastrostomy prior to curative intent treatment were eligible for this single centre randomised controlled trial. Exclusions included severe malnutrition or dysphagia. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 56 publications
2
98
0
4
Order By: Relevance
“…Future research should be aimed at proactive interventions to improve patient's physical and nutritional status, to clarify whether the adverse effects of low SMM are prognostic only, or if they can be overturned by intensive preoperative optimization and postoperative rehabilitation with physical therapy and nutritional support. Feasibility studies in patients with HNC have shown that resistance training programs in patients undergoing chemoradiotherapy or radiotherapy are feasible and show high patient satisfaction . A randomized controlled trial in patients with lung cancer undergoing short‐term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Future research should be aimed at proactive interventions to improve patient's physical and nutritional status, to clarify whether the adverse effects of low SMM are prognostic only, or if they can be overturned by intensive preoperative optimization and postoperative rehabilitation with physical therapy and nutritional support. Feasibility studies in patients with HNC have shown that resistance training programs in patients undergoing chemoradiotherapy or radiotherapy are feasible and show high patient satisfaction . A randomized controlled trial in patients with lung cancer undergoing short‐term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery .…”
Section: Discussionmentioning
confidence: 98%
“…Feasibility studies in patients with HNC have shown that resistance training programs in patients undergoing chemoradiotherapy or radiotherapy are feasible and show high patient satisfaction. 33,34 A randomized controlled trial in patients with lung cancer undergoing short-term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery. 35 However, most current trials are small; larger randomized controlled trials should clarify whether a multimodal rehabilitation program can reduce the negative effects of low SMM in patients undergoing TL.…”
Section: Discussionmentioning
confidence: 99%
“…A logical idea following these results would be to start TF prophylactically in the future. However, this strategy has been investigated by, among others, Brown et al and did not show any beneficial effects on weight loss and health‐related quality of life . In spite of that, Brown showed that early TF can improve patient adherence to clinically indicated TF during treatment .…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesised that this "early tube feeding phase" would reduce fear and anxiety associated with the tube (Merrick & Farrell, 2012), assist patients to adapt to using the tube for when it was required during the "clinical tube feeding phase" to meet nutritional requirements (Salas et al, 2009), and thus result in less weight loss. There was no difference in the primary outcome of weight loss or secondary outcomes including quality of life, nutritional status, body composition, clinical outcomes and survival (Brown et al, 2017a).…”
Section: Introductionmentioning
confidence: 84%
“…Further limitations of this study were that oral intake resumption was used as the reason for A recent randomised controlled trial comparing an early feeding intervention versus standard care in patients with HNSCC and a PGT prior to treatment has been completed to determine the effectiveness of this early intervention on minimising weight loss (Brown et al, 2014b) with the main outcomes reported elsewhere (Brown et al, 2017a). This current study is a planned secondary analysis from this trial to determine whether this early feeding intervention had any impact on longer term tube feeding outcomes.…”
Section: Introductionmentioning
confidence: 99%